2022
DOI: 10.1017/inp.2022.21
|View full text |Cite
|
Sign up to set email alerts
|

Indaziflam reduces downy brome (Bromus tectorum) density and cover five years after treatment in sagebrush-grasslands with no impact on perennial grass cover

Abstract: The invasive annual grass downy brome (Bromus tectorum L.) is a critical threat to the semi-arid shrublands that characterize western North America. More abundant fine fuel after invasion typically increases fire frequency in plant communities adapted to relatively infrequent burning, reducing the likelihood of native plant persistence. Currently, imazapic is most often used to manage B. tectorum, but reinvasion from the seed bank after treatment is common. Indaziflam is a newer herbicide recently labeled for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 74 publications
2
3
0
Order By: Relevance
“…Our results suggest that indaziflam controls ventenata for at least 3 yr post application. Similar to our results, indaziflam effectively controlled other invasive annuals for multiple years (Sebastian et al 2016, 2017b; Courkamp et al 2022). Though ventenata control with indaziflam was substantial in the first yr post application, control improved from yr 1 to yr 2 (see Fig.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results suggest that indaziflam controls ventenata for at least 3 yr post application. Similar to our results, indaziflam effectively controlled other invasive annuals for multiple years (Sebastian et al 2016, 2017b; Courkamp et al 2022). Though ventenata control with indaziflam was substantial in the first yr post application, control improved from yr 1 to yr 2 (see Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Though there appears to be a slight decrease in indaziflam activity by the third yr post application, indaziflam may substantially reduce ventenata in subsequent years. In support of this, indaziflam reduced an exotic annual grass, cheat-grass ( Bromus tectorum L.), for almost 5 yr in Wyoming (Courkamp et al 2022). Clearly, indaziflam controls ventenata and other exotic annual grasses for multiple years, making it an effective management tool to reduce their effects in plant communities.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We found that indaziflam had good efficacy against Bromus tectorum, Bromus japonicus, and Alyssum simplex in both burned and unburned areas during the first growing season post-fire. This indicates successful depletion of the target species' soil seed banks, as reported in other studies (Germino et al 2016b;Sebastian et al 2017;Clark et al 2019;Courkamp et al 2022a) and shows promise for breaking the invader-fire cycle that can develop when annuals degrade historically perennial-dominated vegetation types (Ravi et al 2019;Humphries et al 2021). In terms of species-specific responses to fire at our site, we did not find a post-fire increase in B. tectorum as in other systems (Davies and Nafus 2013).…”
Section: Discussionsupporting
confidence: 86%
“…However, knotroot foxtail biomass totals for the season were greatest for the indaziflam treatment compared with totals for both the nontreated control and pendimethalin (Table 4). Other studies suggest that indaziflam does not negatively affect perennial grass growth (Clark et al 2019(Clark et al , 2020Courkamp et al 2022;Hurdle et al 2020;Sebastian et al 2016Sebastian et al , 2017. Although this may be beneficial for minimizing annual weed competition with bermudagrass forage, it could allow for the further release and spread of knotroot foxtail within bermudagrass pastures.…”
Section: Knotroot Foxtailmentioning
confidence: 99%